Modeling Duration-Based Costing in Activity-Based Costing Software - Lelkes, Anne-Marie Teresa (Journal of Accounting and Finance, 2023)
Can Duration-Based Costing (DBC) and Modified Duration-Based Costing (MDBC) be modeled into an Activity-Based Costing (ABC) software instead of using Excel? Prior research has used Microsoft Excel to model DBC and MDBC. This study builds on prior research regarding the use of DBC and MDBC (Lelkes, 2009, 2014, 2015, 2017; Lelkes & Deis, 2013; Lelkes & Krueger, 2020, 2021) by demonstrating the integration of DBC and MDBC into an ABC software for illustrative purposes, called MyABCM, which is an ABC software that can be standalone or integrated into SAP, Oracle, and other Enterprise Resource Planning (ERP) systems. The case information in this study is adapted from MyABCM training materials and is used to demonstrate how modeling DBC and MDBC appear in MyABCM. MyABCM is used in this study as an example of one of many ways DBC and MDBC can be incorporated into a software that can be integrated into an ERP system. DBC and MDBC can effectively be modeled into any ERP system or standalone ABC software.